PENGARUH CUSTOMER SATISFACTION DAN SWITCHING BARRIERS TERHADAP CUSTOMER LOYALTY (Studi pada Toko Buku Togamas Malang) - Nurmansyah, Doni Alief; Puspaningrum, Astrid (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2015)
The aim of this study is to analyze the effect of customer satisfaction and switching barriers to the customer loyalty of Togamas book store Malang. This design of this study was explanatory research and used 90 respondents as samples. The sampling technique used was purposive sampling by using non-probability sampling method. The instrument was tested by using validation test, reliability test, and classic assumption test (normality test, multicollinearity test, and heteroscedasticity test). The hypothesis was tested by using F test and t test. The data analysis was using multiple linear regression technique. Based on F test, customer satisfaction and switching barriers simultaneously affect significantly to the customer loyalty. Based on t test, customer satisfaction and switching barriers partially affect significantly to the customer loyalty, while customer satisfaction had dominant effect ot he customer loyalty. Keywords: Customer Satisfaction, Switching Barriers, dan Customer Loyalty